Salivary IgA response and upper respiratory tract infection symptoms during a 21-week competitive season in young soccer players - Moreira, A.; Mortatti, A. L.; Arruda, A. F. S.; Freitas, C. G.; de Arruda, M.; Aoki, M. S. (The Journal of Strength and Conditioning Research, 2014)
Sports training and competition are significant sources of stress, especially for young athletes. It is well known that physiological and psychological stressors induce neuroendocrine responses that could modulate immune system function. However, to date, little is known about the immune responses of young soccer players during a competitive season. Therefore, this study examined the effects of a 21-week competitive season divided into preseason, competitive season, and detraining on salivary immunoglobulin A (SIgA), upper respiratory tract infection (URTI) symptoms, and salivary cortisol in preadolescent male soccer players. Thirty-four young soccer players agreed to participate, and 26 (12.9 ± 0.2 years) completed the entire study. The investigation period was structured as follows: a 12-week preparatory training phase (preseason training), a 7-week competitive and a 2-week detraining phase. Resting saliva samples were taken to determine cortisol and SIgA responses. The players were required to complete a weekly log during the entire investigation reporting every sign or symptoms consistent with URTI. A significant increase in SIgA secretion rate and a decrease in URTI symptoms were observed after the 2-week detraining period (p < 0.05). No change was observed for cortisol during the study. These results indicate that training and competition demands affect the mucosal immune responses of young athletes. In addition, a short-prophylactic period (2-week detraining period) after a competitive period may attenuate mucosal immunosuppression related to URTI symptoms. Sport coaches should monitor markers of mucosal immune function to minimize illness that ultimately might lead to a decrease in performance.